2007
DOI: 10.1016/j.anbehav.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees differentially produce novel vocalizations to capture the attention of a human

Abstract: Chimpanzees produce numerous species-atypical signals when raised in captivity. Here we report contextual elements of the use of two captivity-specific vocal signals, the "raspberry" and the extended grunt. Results demonstrate that these vocalizations are not elicited by the presence of food; rather the data suggest that these vocalizations function as attention-getting signals. These findings demonstrate a heretofore underappreciated category of animal signals: novel signals invented in novel environmental ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(199 citation statements)
references
References 37 publications
5
186
0
1
Order By: Relevance
“…Several studies of captive chimpanzees (described above) reported their use of novel vocalizations and nonvocal sounds as voluntarily controlled attention getters with human interactants (Hopkins, et al 2007;Leavens et al 2004Leavens et al , 2010. These learned sounds included an unvoiced raspberry and also a voiced extended grunt, described as a low, loud, guttural sound made with the mouth open (also see Krauss and Fouts 1997, which noted the use of a raspberry as an attention getter by a sign-taught chimpanzee).…”
Section: Vocal Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies of captive chimpanzees (described above) reported their use of novel vocalizations and nonvocal sounds as voluntarily controlled attention getters with human interactants (Hopkins, et al 2007;Leavens et al 2004Leavens et al , 2010. These learned sounds included an unvoiced raspberry and also a voiced extended grunt, described as a low, loud, guttural sound made with the mouth open (also see Krauss and Fouts 1997, which noted the use of a raspberry as an attention getter by a sign-taught chimpanzee).…”
Section: Vocal Learningmentioning
confidence: 99%
“…A set of studies found that captive chimpanzees housed at the Yerkes National Primate Research Center were more likely to use manual gestures to communicate with a visually attentive experimenter, but were more inclined to produce vocalizations and non-vocal sounds when the experimenter was inattentive or facing away (Hopkins et al 2007;Leavens et al 2004Leavens et al , 2010. For example, chimpanzees tactically employed vocalizations in the service of gaining the attention of an inattentive human interlocutor with access to food.…”
Section: Vocal Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonhuman primates do show some modification of vocal output, but this seems to be based largely on modification of innate calls through altering positioning of the mouth or lips rather than through control of the larynx. For instance, chimpanzees can produce novel sounds to attract attention by puckering and vibrating their lips to create a "raspberry" sound (Hopkins, Taglialatela, & Leavens, 2007), and captive orangutans (Pongo pygmaeus) have spontaneously matched human whistles (Lameira et al, 2013). In contrast, in humans there is precise control of voicing itself, allowing for a far wider repertoire of different learned patterns.…”
Section: Vocal Learningmentioning
confidence: 99%
“…However, aside from a report of a captive orangutan imitating a human whistle without explicit training [Wich et al, 2008], there is no evidence that non-human primates invent new vocalizations without extensive human contact or human enculturation. Additionally, there is only limited evidence of flexible call production or usage outside of fixed social contexts [Hopkins et al, 2007;Janik & Slater, 2000;Marshall et al, 1999;Mitani & Brandt, 1994;Ouattara et al, 2009a;Seyfarth & Cheney, 1997;Seyfarth et al, 1980;Snowdon & Hodun, 1981;Tomasello & Zuberbühler, 2002]. Creating new signals and using them in multiple contexts are key aspects of human language, yet these phenomena are not pervasive in non-human primate vocal communication.…”
Section: Introductionmentioning
confidence: 99%